Modul Pembelajaran Matematika Bernuansa Islami dengan Pendekatan Inkuiri - Diana, Mulia; Netriwati, Netriwati; Suri, Fraulein Intan (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to produce teaching materials in the form of islamic mathematics learning module through guided inquiry approach in the setting set subject. This research method is Borg and Gall method that modified by Sugiyono. Stages performed only from stage 1 to stage 7 of potential and problems, data collection, product design, product validation, product revision, product trial, product revision. Based on the validation of material experts obtained the results of 80.83%, media experts obtained 88.89%, linguists obtained 80.95%, Islamic scholars obtained 76.67% thus developed products declared eligible for use. After validation of the product to the expert lecturer then the product is tested by educator in the field of mathematics study and the learner. Response educator in the field of mathematics study Obtained percentage of 85.49% with the criteria